Prevention method of toric intraocular lens rotation after phacoemulsification of cataract using a standard capsule ring - Zavgorodnya, N. G.; Novikova, V. Yu. (Journal of Education, Health and Sport, 2021)
At the same time, phacoemulsification of cataracts remains the most popular surgery. But the problem among phacosurgeons is the correction of existing corneal astigmatism. According to studies, about 30% of the world's population have corneal astigmatism with a strength of 0.75D and above, which leads to a decrease in visual acuity after phacoemulsification of cataracts in the absence of its correction. The most commonly used method to correct corneal astigmatism is the implantation of toric intraocular lenses (TIOL). The main condition for obtaining high visual acuity after TIOL implantation is the location of the astigmatic component of the artificial lens in accordance with the strong meridian of the cornea. The aim of this study was to evaluate the effectiveness of the proposed method of preventing the toric intraocular lens rotation after phacoemulsification of cataracts in the eyes with corneal astigmatism by implantation of a standart capsule ring. Material and methods. The article presents the results of a comprehensive examination of 43 patients (59 eyes) who underwent surgery by phacoemulsification of cataracts with implantation of toric IOL to correct concomitant corneal astigmatism. Corneal astigmatism according to keratometry ranged from 0.5D to 4.25D (average 1.96 ± 0.1 D). Patients were divided into 2 groups. The first group consisted of 26 patients (31 eyes). Patients in this group underwent phacoemulsification with toric IOL implantation according to standard techniques without the use of techniques that prevent rotation of the artificial lens in the postoperative period. The second group included 18 patients (28 eyes) who were operated on according to our proposed prevention method of TIOL rotation. As a result of the study, it was found that rotation of TIOL was detected 6 months after surgery in the I group without the use of developed method in 22 eyes (70.9%), in the II group, where the capsule ring was implanted, rotation occurred in 12 eyes (42.85%). In the II group in all cases, the deviation of the TIOL axis did not exceed 6 degrees. The proposed method of prevention of rotation of TIOL allows to increase the efficiency of phacoemulsification of cataracts. Conclusions. Developed a method of preventing the rotation of the toric intraocular lens using a standard capsule ring, which is implanted and located on top of the haptic support elements of the artificial lens can increase the efficiency of phacoemulsification of cataracts in the eyes with corneal astigmatism, contributes to the rotational stability of the toric lens and provides long-term results of visual functions, reduces the need for repeated surgery due to reposition of the rotated lens and can be recommended for implementation in the practice of ophthalmic surgeons. The use of implantation of a standard capsule ring according to the proposed in this study method prevents the rotation of the toric intraocular lens by more than 6 degrees in all cases, which does not significantly reduce visual acuity and does not require reposition of the artificial lens. This method of preventing rotation of the toric intraocular lens allows to achieve visual acuity of 0.7 and above in 85.6% of cases.